2015
DOI: 10.1002/path.4548
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage PPARγ and impaired wound healing in type 2 diabetes

Abstract: Macrophages undergo a transition from pro-inflammatory to healing-associated phenotypes that is critical for efficient wound healing. However, the regulation of this transition during normal and impaired healing remains to be elucidated. In our studies, the switch in macrophage phenotypes during skin wound healing was associated with upregulation of the peroxisome proliferator-activated receptor (PPAR)-γ and its downstream targets, along with increased mitochondrial content. In the setting of diabetes, upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 61 publications
4
115
0
1
Order By: Relevance
“…This supports the current paradigm of the M1-M2 switch [1,15]. If the M1-M2 transition does not occur, nonhealing or chronic wounds such as venous ulcers and diabetic wounds are the result [16,17,18]. These observations underpin the intimate and important role of macrophages throughout the process of skin wound healing.…”
Section: From Inflammation To Proliferationsupporting
confidence: 57%
“…This supports the current paradigm of the M1-M2 switch [1,15]. If the M1-M2 transition does not occur, nonhealing or chronic wounds such as venous ulcers and diabetic wounds are the result [16,17,18]. These observations underpin the intimate and important role of macrophages throughout the process of skin wound healing.…”
Section: From Inflammation To Proliferationsupporting
confidence: 57%
“…Since IL-1β is predominantly produced by monocytes and macrophages (Mirza, Fang et al 2015), use of an inflammasome inhibitor to lower IL-1β expression may be an appealing anti-inflammatory strategy since these inflammatory cells are key regulators of the wound healing process (Koh and DiPietro 2011). Notably, treatment of excisional wounds on db/db diabetic mice with topical glyburide was shown to accelerate epithelialization and increase granulation tissue formation.…”
Section: Sulfonylureasmentioning
confidence: 99%
“…Recent studies have reported that topical treatment of wounds on db/db diabetic mice with rosiglitazone reported improved wound healing by inducing a switch of pro-inflammatory macrophages towards a pro-healing phenotype (Mirza, Fang et al 2015). They also found that diabetic wounds from mouse and human patients showed impaired PPAR-γ activity due to sustained expression of IL-1β, which maintained wounds in a persistent inflammatory state.…”
Section: Thiazolidinedionesmentioning
confidence: 99%
See 2 more Smart Citations